Investigation of Thermal Properties of Half-Heusler Alloy FeVZ (Z= As, P, Sb) within Density Functional Theory - Anugrah Azhar (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2021)
The figure of merit (ZT) holds an important role in thermoelectric material that indicates the efficiency of thermoelectric (TE) devices. The higher ZT value, the higher efficiency would be obtained of TE devices. One of the sub-class materials that has high potential application for thermoelectric material is half-Heusler (HH) alloy. In order to investigate the ZT value of HH conduct simulation using to investigate the ZT value of HH alloy FeVZ (Z= As, P, Sb) by using density-functional theory (DFT). Our research results show that FeVAs has higher ZT values than FeVP and FeVSb in the range temperature of 150-900 K. All of those compounds still have good ZT value around ~0.7 even in the temperature regime of 900 K, and shows a good trend for p-type thermoelectric materials.